Exlibris Zofii Nałkowskiej 1884-1954 / Dolatowski. - Dolatowski, Zbigniew (1927-2001) ([wydawca nieznany], 1954)
W owalnej ramie napis: Exlibris Zofii Nałkowskiej 1884-1954. Sygnatura artysty w obrębie kompozycji.